GEOGRAPHICAL CONDITIONS AND TOURIST FEATURES OF THE LOWER REACH OF THE CHATKAL RIVER - Abdullaev Ilkhom Khatamovich; Ubaydullaeva Shodiya Ravshan kizi (Journals Park Publishing, 2023)
This article discusses the geographical features of the lower reaches of the Chatkal River, the sights and tourist features of the main large tributaries, and also describes the tourist routes of individual territories.
Keywords: geographical conditions, recreation, tourism, reservoir, river, tourist route, canyon, landmark, waterfall.